The crain adventure: the making and building of a family publishing company - Goldsborough, Robert (Illinois: NTC Publishing Group, 1992)
Contents: part 1. it all began in louisville. part 2. the birth of a giant. Part 3. War, recovery and boom. part 4. new publications, new challengens. part 5. broadering the horizons.
Index p. 128 - 132
Keywords: Gestión de Medios - Publicidad